Spatial and temporal expansion of intrahepatic metastasis by molecularly‐defined clonality in multiple liver cancers. Issue 2 (11th January 2020) - Yamamoto, Shogo; Midorikawa, Yutaka; Nagae, Genta; Tatsuno, Kenji; Ueda, Hiroki; Moriyama, Mitsuhiko; Takayama, Tadatoshi; Aburatani, Hiroyuki
Abstract: Multiple hepatocellular carcinoma (HCC) is divided into two categories: intrahepatic metastasis (IM), which is a true relapse of HCC, and multicentric origin (MO), which is a second primary tumor. Clinical diagnosis of multiple HCC is usually made based on tumor location and/or time to recurrence; however, it is often difficult to distinguish the two types of multiple HCC. Using 41 matched pairs of multiple HCC specimens, we confirmed the accuracy of clinical diagnoses using exome sequence data and investigated the importance of discriminating the type of multiple HCC. Genomic analysis revealed that 18 (43.9%) patients diagnosed as having genomic IM had common mutations in a pair of HCC tumors with the main tumor of these patients being more progressive compared to those with genomic MO. The accuracy of clinical diagnosis based on lobe (Definition 1) and segment (Definition 2) were 68.3% and 78.0%, respectively. Intriguingly, recurrence ≥2 years after initial surgery for 3 patients was IM. The survival of patients with clinical IM was significantly shorter than for those with clinical MO based on both Definition 1 ( P = 0.045) and Definition 2 ( P = 0.043). However, mean survival was not different between the patients with genomic IM and those with MO ( P = 0.364). Taken together, genomic analysis elucidated that liver cancer may spread more extensively and more slowly than previously thought. In addition, distinguishing multiple HCC as IM or MC may have provided biological information but was not of clinical importance with respect to patient prognosis. Abstract : Exome sequencing was able to be used to discriminate multiple HCC as IM or MO and it became clear that liver cancer cells could spread more extensively and more slowly than previously thought. Given that the overall survival of patients with IM and MO did not differ, the accurate classification of multiple HCC is not clinically important.